The skin lightening properties of mushrooms: A comprehensive review of mechanisms and applications - Reetu; Rahul Jaiswal; Sageer Ahmad; Vijayshwari Mishra; Supriya Pandey; Ashutosh Kumar Yadav; Asad Ali; Rupali Jaiswal; Reema Yadav; Rabiya Ahsan; Tapasya Dwivedi; Sonali; et al. (Next Research, 2026)

A modified semi-quantitative framework for assessing the impacts and sustainability of iron ore mining in a biodiverse forest - Rahul Kumar; Ashish Kumar; Pranjal Pathak; Biswajit Samanta (Environmental Development, 2026)

Interfacial-bulk electrochemistry of sodium-ion storage in multiwalled carbon nanofiber anode with incorporated Mn−N4 single-atoms - Anubha Yadav; Prakash Kumar Pathak; Babasaheb M. Matsagar; Rahul Patil; Norman C.-R. Chen; Rajashri R. Urkude; Masaki Ujihara; Kevin C.-W. Wu; Rahul R. Salunkhe; Saikat Dutta (Chemical Engineering Journal, 2025)

Artemisinin’s molecular symphony: illuminating pathways for cancer therapy - Sandeep Kumar Jhade; Karthik Kalidoss; Poonam Kumari Pathak; Rahul Shrivastava (Molecular Biology Reports, 2025)

Endophytic Bacillus inaquosorum and Bacillus safensis Enhanced Growth, Proline Content and Antioxidant Enzymes in Avena sativa L. Under Salt Stress - Arshdeep Kaur; Pratibha Vyas; Namarta Gupta; Rahul Kapoor; Loveena Pathak (Current Microbiology, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Metabolic dysregulation in amyotrophic lateral sclerosis: insights from 1H NMR-based metabolomics in a tertiary care center in India - Priyanka Gautam; Rahul Yadav; Ranjeet Kumar Vishwakarma; Abhishek Pathak; Chandan Singh (Metabolic Brain Disease, 2025)

Geospatial mapping of groundwater potential zones using multi-criteria decision-making AHP approach: A study of Kadugli district, south Kurdufan, Sudan - Majdi Sultan Hamdan; Rakesh Singh; Rahul Pathak; Shalini Kumari; Vishal Chauhan (Journal of African Earth Sciences, 2025)

Illigera Grandiflora W.W. Sm. & Jeffrey (Hernandiaceae): a potent source of antioxidants and in silico molecular docking analysis as vascular endothelial growth factor (VEGF) pathway regulator - Ashutosh Pathak; Rahul Das; Deepu Vijayan; Nripemo Odyuo; David Lalsama Baite; Ashiho Asosii Mao (Vegetos, 2025)

A green and economic approach to synthesize magnetic Lagenaria siceraria biochar (γ-Fe2O3-LSB) for methylene blue removal from aqueous solution - Ayushi Mishra; Jyoti Pandey; Himanshu Ojha; Malti Sharma; Lajpreet Kaur; Akhilesh Pandey; Pankaj Sharma; Sumit Murab; Rahul Singhal; Mallika Pathak (Environmental Science and Pollution Research, 2024)

Fatty Acids and their Proteins in Adipose Tissue Inflammation - Rahul Mallick; Sanjay Basak; Ranjit K. Das; Antara Banerjee; Sujay Paul; Surajit Pathak; Asim K. Duttaroy (Cell Biochemistry and Biophysics, 2024)
Chronic low-grade adipose tissue inflammation is associated with metabolic disorders. Inflammation results from the intertwined cross-talks of pro-inflammatory and anti-inflammatory pathways in the immune response of adipose tissue. In addition, adipose FABP4 levels and lipid droplet proteins are involved in systemic and tissue inflammation. Dysregulated adipocytes help infiltrate immune cells derived from bone marrow responsible for producing cytokines and chemokines. When adipose tissue expands in excess, adipocyte exhibits increased secretion of adipokines and is implicated in metabolic disturbances due to the release of free fatty acids. This review presents an emerging concept in adipose tissue fat metabolism, fatty acid handling and binding proteins, and lipid droplet proteins and their involvement in inflammatory disorders.

Carbon and water footprints of major crop production in India - Amaresh Kumar NAYAK; Rahul TRIPATHI; Manish DEBNATH; Chinmaya Kumar SWAIN; Biswaranjan DHAL; Shanmugam VIJAYKUMAR; Anshuman Debasis NAYAK; Sangita MOHANTY; Mohammad SHAHID; Anjani KUMAR; Manoj RAJAK; Khitish Chandra MOHARANA; et al. (Pedosphere, 2023)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Calcareous peloids in the north-western Arabian Sea: implications of late Quaternary marine sedimentation and paleoclimate - Vikas Dev; Vishwesh Kumar Pathak; Rahul Dey; Madhurima Mazumder; Ajai Kumar Rai; Siddhartha Sankar Das (Arabian Journal of Geosciences, 2022)

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Solubility-Modulated Asymmetric Membrane Tablets of Triprolidine Hydrochloride: Statistical Optimization and Evaluation - Rahul Dev; Anil Kumar; Kamla Pathak (AAPS PharmSciTech, 2012)

Altered phosphorylation and distribution status of vimentin in rat seminiferous epithelium following 17β-estradiol treatment - Rahul Upadhyay; Ryan D’Souza; Shobha Sonawane; Reshma Gaonkar; Shilpa Pathak; Aditi Jhadav; N. H. Balasinor (Histochemistry and Cell Biology, 2011)

Ameliorating effect of N-acetylcysteine and curcumin on pesticide-induced oxidative DNA damage in human peripheral blood mononuclear cells - Tanzeel Ahmed; Rahul Pathak; MD. Mustafa; Rajarshi Kar; Ashok K. Tripathi; Rafat S. Ahmed; B. D. Banerjee (Environmental Monitoring and Assessment, 2011)

Maternal and cord blood levels of Aldrin and Dieldrin in Delhi population - MD. Mustafa; Rahul Pathak; A. K. Tripathi; Rafat S. Ahmed; Kiran Guleria; B. D. Banerjee (Environmental Monitoring and Assessment, 2010)

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population - Rahul Pathak; Sanvidhan G. Suke; Rafat S. Ahmed; A. K. Tripathi; Kiran Guleria; C. S. Sharma; S. D. Makhijani; Meenu Mishra; B. D. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2008)